Endogenous regeneration after collagenase-induced knee joint damage in the adult newt Notophthalmus viridescens. Issue 1 (31st August 2010) - Geyer, Matthias; Borchardt, Thilo; Schreiyäck, Carina; Wietelmann, Astrid; Müller-Schrobsdorff, Florian; Müller, Clemens; Müller-Ladner, Ulf; Dinser, Robert
Abstract : Objectives: To determine whether adult newts ( Notophthalmus viridescens ) are able to repair experimentally-induced joint damage in order to generate a model system for the study of endogenous joint regeneration. Methods: Joint instability and articular cartilage lesions of the knee joint of adult newts ( N viridescens ) were induced by intra-articular injection of collagenase. The changes over time were analysed clinically, by MRI, histologically and by reverse transcription PCR to detect selected relevant markers. Results: After rapid onset of disease with joint luxation, loss of proteoglycans and cartilage volume, the signs ameliorated continuously by regeneration of the affected joint compartments. The majority of joints were morphologically intact and functionally operative after 10 weeks. Upregulation of chondrogenic key genes, homogenous expression levels of factors implicated in cartilage homeostasis and limb regeneration as well as the distribution of the blastemal marker 22/18 in both treated and untreated knees suggest that joint regeneration in adult newts only partially invokes pathways of embryological organogenesis. Conclusions: Newts are able to regenerate articular cartilage injuries and to restore tissue integrity and function after induction of damage using a procedure known to induce experimental osteoarthritis in murine models. Further analysis of the underlying molecular mechanisms may contribute to the development of novel treatment approaches in joint failure.